Tracheobronchoplasty for malacia (Revista Argentina de Cirugía, 2021)
Tracheobroncomalacia is a disease of the central airway due to weakness of the wall with dynamicnarrowing of the lumen of the trachea and mainstem bronchi during exhalation. It produces chronicsymptoms that can progress to severe respiratory failure, often misdiagnosed as asthma or chronicobstructive pulmonary disease (COPD). We report the case of a 70-year-old female patient with ahistory of rheumatoid arthritis and multiple hospitalizations for recurrent respiratory infections overthe past 3 years.
Keywords: tracheoplasty; tracheomalacia; tracheobronchomalacia